2006
DOI: 10.1097/01.ede.0000231546.14749.ab
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculin Reaction, BCG Scar, and Lower Female Mortality

Abstract: A good response to BCG vaccination is related to lower child mortality. The effect seems most pronounced among girls. The findings may have implications for future vaccine trials and policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 32 publications
5
58
0
1
Order By: Relevance
“…Our group has consistently found that vaccines, apart from disease-specific effects, may also have so-called "nonspecific effects." The live vaccines bacille Calmette-Guérin (BCG), which is recommended at birth, and measles vaccine (MV), which is recommended at 9 mo of age, are associated with decreased overall mortality (14)(15)(16)(17), whereas diphtheria-tetanus-pertussis vaccine (DTP), which is recommended at 6, 10, and 14 wk of age, is associated with increased mortality in areas where exposure to pertussis is limited because of high vaccination coverage (18)(19)(20). Intriguingly, both beneficial and negative effects of vaccines have been strongest in girls (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Our group has consistently found that vaccines, apart from disease-specific effects, may also have so-called "nonspecific effects." The live vaccines bacille Calmette-Guérin (BCG), which is recommended at birth, and measles vaccine (MV), which is recommended at 9 mo of age, are associated with decreased overall mortality (14)(15)(16)(17), whereas diphtheria-tetanus-pertussis vaccine (DTP), which is recommended at 6, 10, and 14 wk of age, is associated with increased mortality in areas where exposure to pertussis is limited because of high vaccination coverage (18)(19)(20). Intriguingly, both beneficial and negative effects of vaccines have been strongest in girls (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Among BCG-vaccinated children, those having a BCG scar or a positive tuberculin test have lower mortality. 4,6,7 The mechanisms behind these non-specific effects remain unclear. Several studies in humans have observed increased T helper type 1 (Th1) responses, [8][9][10] and at times also Th2 responses, [11][12][13] following BCG vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Albeit conflicting results, studies have shown effects that cannot be attributed to the protection of tuberculosis and a stronger effect for girls compared with boys. [29][30][31][32] On the contrary, previous studies on BCG and T1D found no association, 27,33 but the evidence remains inconsistent. 34 In our study, BCG vaccination was significantly associated with decreased risk for CD (adjusted OR 0.54), but with no difference between girls and boys.…”
Section: Figurementioning
confidence: 89%